تطوير تعليم المفردات باستخدام بطاقة أونو في المدرسة الثانوية الحكومية ليما بولوه كوتا - Nur Illahi, Citra; Salam, Muhammad Yusuf; Taman, Mona (Journal of Arabic Language Teaching, 2024)
The objectives of this study are: (1) to determine the need for UNO Card media for vocabulary teaching in reading among students at MTsN 7 Lima Puluh Kota, (2) to ascertain the validation of UNO Cards at MTsN 7 Lima Puluh Kota, (3) to determine the practicality of using UNO Cards at Madrasah Tsanawiyah Negeri (MTsN) 7 Lima Puluh Kota. The method used in this research is developmental research (R&D). The development model used is the 4-D design: Define, Design, Development, and Disseminate. The results of this study are as follows: (1) UNO cards are beneficial and meet the needs of teachers in teaching vocabulary for reading Arabic texts. (2) The validation results of UNO Cards indicate they are highly valid with the following details: (a) Methodology expert validation with a percentage of 92% and the score is very accurate, (b) language expert validation at 80% and the score is correct, (c) and validation by subject matter experts at 95%, and the score is very accurate. The overall results indicate that the product validation shows an average score of 89%. This score indicates that the UNO card design is highly valid. (3) The results of using UNO cards are (a) teacher questionnaire responses at 92% and (b) student questionnaire responses at 94%, both indicating that the cards are convenient.